Rehabilitation Recommendations for Adult Patients with COVID-19: Recomendaciones para la Rehabilitación de Pacientes Adultos con COVID-19 - De la Cerna Luna, Roger (2021)
Introduction: The SARS-CoV-2 coronavirus is a new pathogen causing COVID-19 disease, ranging from an asymptomatic infection to a critical condition dependent on mechanical ventilation. Rehabilitation interventions contribute for the prevention and treatment of related complications and associated disability. Objective: Evaluate the rehabilitation interventions for the care of patients with COVID-19 according to the available evidence. Methods: A systematic review was conducted through electronic and library searches of national and foreign medical journals over a 10-year horizon in Spanish, English, Chinese and Italian, as well as in textbooks with information related to COVID-19 and Physical Medicine and Rehabilitation. Conclusions: Rehabilitation interventions are essential and indispensable resources for the transdisciplinary treatment of patients with COVID-19, despite of the low quality of the available evidence.